Atributos de um Argissolo Amarelo coeso sob cultivo de cafeeiro a pleno sol e consorciado com espécies arbóreas - Pilon, Lucas Contarato (2013)
Faced with the need for information on the coffee agroforestry systems, the objective is to evaluate the relationship of the chemical, physical and components of soil organic matter under coffee intercropping with different tree species, compared to the f